Clustering of Olive Pollens into Model Cultivars on the Basis of Their Allergenic Content - Morales, Sonia; Castro, Antonio Jesús; Salmerón, Carmen; Marco, Francisco Manuel; Rodríguez-García, María Isabel; Alche, Juan de Dios (IntechOpen, 2012)
None